Tap For Battle: Perancangan Casual Game Pada Smartphone Android - Chowanda, Andry; Prabowo, Benard H.; Iglesias, Glen; Diansari, Marsella (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Smartphones have become a necessity. Almost everyone uses a smartphone in a variety of activities. Both young and old are sure to utilize this technology, for a wide range of activities such as doing the work, doing school work or enjoying entertainment. The purpose of this research is to build a casual-action game with war theme. The game is built for Android smartphone that has multi touch screen capability. The research methods used in this research are data collection and analysis method including user analysis with questionnaire. Furthermore, IMSDD method is implemented for game design and development phase including system requirement analysis, system design, system implementation, finally system evaluation. In this research, we conclude that 83.9% participants enjoyed the game with touch-screen as the game control.